2022
DOI: 10.1111/aogs.14379
|View full text |Cite
|
Sign up to set email alerts
|

Different segmental resection techniques and postoperative complications in patients with colorectal endometriosis: A systematic review

Abstract: Introduction The aim of this study was to analyze the available literature by conducting a systematic review to assess the possible effects of nerve‐sparing segmental resection and conventional bowel resection on postoperative complications for the treatment of colorectal endometriosis. Material and methods Pubmed, Clinical http://trials.gov, Cochrane Library, and Web of Science were comprehensively searched from 1997 to 2021 in order to perform a systematic review. Studies including patients undergoing segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 80 publications
(177 reference statements)
3
14
0
Order By: Relevance
“…More specifically, no rectovaginal, ureteral, or vesicovaginal fistulas were reported, nor was there ureteral or colorectal anastomosis stenosis. These data findings are consistent with what was reported in a recent review by Darici et al, 8 which showed a rate between 0% and 3.6% for rectovaginal fistulas and between 0% and 6.1% for ureteral fistulas in the group of patients undergoing segmental resection using nerve-and vascular-sparing techniques.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…More specifically, no rectovaginal, ureteral, or vesicovaginal fistulas were reported, nor was there ureteral or colorectal anastomosis stenosis. These data findings are consistent with what was reported in a recent review by Darici et al, 8 which showed a rate between 0% and 3.6% for rectovaginal fistulas and between 0% and 6.1% for ureteral fistulas in the group of patients undergoing segmental resection using nerve-and vascular-sparing techniques.…”
Section: Discussionsupporting
confidence: 93%
“…9 However, there is no adequate evidence to establish its superiority compared with the classic technique. 8 In our series, there were no major Clavien-Dindo complications 3 or 4. More specifically, no rectovaginal, ureteral, or vesicovaginal fistulas were reported, nor was there ureteral or colorectal anastomosis stenosis.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Taking into account anastomotic height as a main factor for risk of leakage and rectovaginal fistula, a retrospective multicenter study was unable to support this view when complication rates of FTDR using transanal staplers were compared with a modified nerve and vessel sparing technique for segmental resection (NVSSR) in women undergoing low resections for colorectal DE 14 . Within this, a recent systematic review on differences in surgical techniques of segmental resection for colorectal DE concluded that data so far were inhomogeneous and insufficient to show a proven advantage of nerve and nerve plus vessel sparing approaches 15 . The primary aim of the present study was to further investigate changes in pre‐ and postsurgical GI function following a modified nerve and vessel sparing segmental resection (NVSSR) method compared with FTDR.…”
Section: Introductionmentioning
confidence: 99%